Application of nanoparticles in the diagnosis and treatment of chronic kidney disease - Yang, Kaibi; Shang, Yiwei; Yang, Nan; Pan, Shujun; Jin, Juan; He, Qiang (Frontiers in Medicine, 2023)
With the development of nanotechnology, nanoparticles have been used in various industries. In medicine, nanoparticles have been used in the diagnosis and treatment of diseases. The kidney is an important organ for waste excretion and maintaining the balance of the internal environment; it filters various metabolic wastes. Kidney dysfunction may result in the accumulation of excess water and various toxins in the body without being discharged, leading to complications and life-threatening conditions. Based on their physical and chemical properties, nanoparticles can enter cells and cross biological barriers to reach the kidneys and therefore, can be used in the diagnosis and treatment of chronic kidney disease (CKD). In the first search, we used the English terms “Renal Insufficiency, Chronic” [Mesh] as the subject word and terms such as “Chronic Renal Insufficiencies,” “Chronic Renal Insufficiency,” “Chronic Kidney Diseases,” “Kidney Disease, Chronic,” “Renal Disease, Chronic” as free words. In the second search, we used “Nanoparticles” [Mesh] as the subject word and “Nanocrystalline Materials,” “Materials, Nanocrystalline,” “Nanocrystals,” and others as free words. The relevant literature was searched and read. Moreover, we analyzed and summarized the application and mechanism of nanoparticles in the diagnosis of CKD, application of nanoparticles in the diagnosis and treatment of renal fibrosis and vascular calcification (VC), and their clinical application in patients undergoing dialysis. Specifically, we found that nanoparticles can detect CKD in the early stages in a variety of ways, such as via breath sensors that detect gases and biosensors that detect urine and can be used as a contrast agent to avoid kidney damage. In addition, nanoparticles can be used to treat and reverse renal fibrosis, as well as detect and treat VC in patients with early CKD. Simultaneously, nanoparticles can improve safety and convenience for patients undergoing dialysis. Finally, we summarize the current advantages and limitations of nanoparticles applied to CKD as well as their future prospects.